A review of risk-based approaches for emerging diseases associated with animal-source foods - Grace, Delia; Omore, Amos O.; Randolph, Thomas F.; Hussni, M.O. (African Journals Online, 2007)
Rapid urbanization, globalization and intensification of livestock production in developing countries are causing dramatic changes in food production, supply and consumption with the potential of generating unprecedented opportunities for poor farmers, processors and traders. But, changing production systems and eco-systems also offer new niches for emerging and re-emerging diseases. Animal source food, though an excellent source of protein and micro-nutrients, is also the single most important source of food-borne disease. This paper reviews risk-based approaches for better management of foodborne diseases in developing countries, with an emphasis on local markets and emerging diseases. Methodologies developed by the Codex Alimentarius Commission (CAC) are explained. The benefits of risk-based approaches as well as the challenges of adapting them are discussed using examples from ongoing case-studies involving emerging food borne diseases in East and West Africa.